Pemisahan Anomali Gayaberat Regional dan Residual Menggunakan Metode Gaussian Low Pass Filter pada Daerah Potensi Panas Bumi Way Ratai Lampung - Agustian, Rizki Buana; Amanda, Anisa; Fista, Aksela Dian; Dani, Ilham (Jurnal Teras Fisika: Teori, Modeling, dan Aplikasi Fisika, 2025)
This study aims to separate regional and residual components from complete Bouguer anomaly data using the Gaussian Low Pass Filter method in the geothermal prospect area of Way Ratai, Lampung. Spectral analysis was applied to determine the optimal cutoff frequency that distinguishes regional, residual, and noise components. The spectrum analysis identified three linear segments with R² values of 0.8332 (regional), 0.9655 (residual), and 0.9518 (noise), supporting the accuracy of the segmentation. The complete Bouguer anomaly map displays a decreasing gravity trend towards the northeast, indicating large-scale subsurface density variations. After filtering, the regional anomaly map shows smooth contours reflecting broader geological structures, while the residual anomaly map reveals sharper local features such as faults and fractures, which are potential geothermal fluid pathways. These results demonstrate the effectiveness of the Gaussian Low Pass Filter in enhancing geophysical resolution and geological interpretation for geothermal exploration.